Hedgehog Pathway Inhibition by Novel Small Molecules Impairs Melanoma Cell Migration and Invasion under Hypoxia - Alessandro Falsini; Gaia Giuntini; Mattia Mori; Francesca Ghirga; Deborah Quaglio; Antonino Cucinotta; Federica Coppola; Irene Filippi; Antonella Naldini; Bruno Botta; Fabio Carraro (Pharmaceuticals, 2024)
Melanoma is the principal cause of death in skin cancer due to its ability to invade and cause metastasis. Hypoxia, which characterises the tumour microenvironment (TME), plays an important role in melanoma development, as cancer cells can adapt and acquire a more aggressive phenotype. Carbonic anhydrases (CA) activity, involved in pH regulation, is related to melanoma cell migration and invasion. Furthermore, the Hedgehog (Hh) pathway, already known for its role in physiological processes, is a pivotal character in cancer cell growth and can represent a promising pharmacological target. In this study, we targeted Hh pathway components with cyclopamine, glabrescione B and C22 in order to observe their effect on carbonic anhydrase XII (CAXII) expression especially under hypoxia. We then performed a migration and invasion assay on two melanoma cell lines (SK-MEL-28 and A375) where Smoothened, the upstream protein involved in Hh regulation, and GLI1, the main transcription factor that determines Hh pathway activation, were chemically inhibited. Data suggest the existence of a relationship between CAXII, hypoxia and the Hedgehog pathway demonstrating that the chemical inhibition of the Hh pathway and CAXII reduction resulted in melanoma migration and invasion impairment especially under hypoxia. As in recent years drug resistance to small molecules has arisen, the development of new chemical compounds is crucial. The multitarget Hh inhibitor C22 proved to be effective without signs of cytotoxicity and, for this reason, it can represent a promising compound for future studies, with the aim to reach a better melanoma disease management.